Uncertainty Evaluation in Measurement Equipments for Power Systems - Peretto, Lorenzo; Tinarelli, Roberto; Yigit, Kenan (IEEE, 2016)
This paper presents the study of the propagation of the effects of uncertainties arising in two key elements of a measurement equipment for modern power systems. The first element is the LPIT (Low Power Instrument Transformer), which is the first element of the measurement chain that converts the primary quantities (voltage, current) into a low-value, low power voltage. The second element is the SAMU (Stand Alone Merging Unit), which collects all voltages from LPIT outputs and converts them into digital form, according to the 61850-9-2 protocol. The characteristics of the LPIT and SAMU will be described in the next IEC Standards 61869-6 and 61869-13, respectively. Both Standards are in the final stage of their preparation. In particular, in 61869-13 a Section is dedicated to the method (suitable and comprehensible by system operators) for evaluating the combined standard uncertainty of LPIT-SAMU. In this paper such a method will be presented along with its use and implementation in practical applications.
Keywords: uncertainty; smart grid; accuracy class; FUZZY APPROACH; Energy & Fuels; Engineering